Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1172/jci67399
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step inhibition explains HIV-1 protease inhibitor pharmacodynamics and resistance

Abstract: HIV-1 protease inhibitors (PIs) are among the most effective antiretroviral drugs. They are characterized by highly cooperative dose-response curves that are not explained by current pharmacodynamic theory. An unresolved problem affecting the clinical use of PIs is that patients who fail PI-containing regimens often have virus that lacks protease mutations, in apparent violation of fundamental evolutionary theory. Here, we show that these unresolved issues can be explained through analysis of the effects of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 67 publications
5
126
0
Order By: Relevance
“…Antiretroviral drugs that act at multiple steps of the HIV-1 life cycle have nonlinear dose-response curves with steep slopes (12), which yield high efficacy at clinical concentrations (10)(11)(12). Both inocula A and B have DTG dose-response curves with slopes of 1.3 ± 0.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiretroviral drugs that act at multiple steps of the HIV-1 life cycle have nonlinear dose-response curves with steep slopes (12), which yield high efficacy at clinical concentrations (10)(11)(12). Both inocula A and B have DTG dose-response curves with slopes of 1.3 ± 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…Although frequently overlooked, slope is an important determinant of efficacy because of its exponential relationship with inhibition (10,11). High slopes for HIV-1 protease inhibitors (12) and allosteric integrase inhibitors (ALLINIs) (13)(14)(15)(16)(17) reflect inhibition at multiple steps in the viral life cycle. The first-generation InSTI raltegravir has not shown activity at HIV-1 life cycle steps other than integration (13)(14)(15), but DTG has not been evaluated for such activity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified changes in gp41 of the envelope gene as an alternate route of PI resistance suggesting that sites outside of PR and Gag may also be involved. 35 Others have suggested that due to the short half life of PIs, there is a limited mutation selection window such that wild-type virus emerges faster than mutant virus resulting in the restricted evolution of drug resistance. 36 Thus further studies are needed to determine the reasons why patients fail PIs in the absence of detectable resistance mutations.…”
Section: Figmentioning
confidence: 99%
“…The observations of Rabi et al shed new light on the inhibition of the HIV life cycle and alternative mechanisms of resistance to PIs (7). First, the authors have utilized a series of clever experiments to identify the inhibitory effect of PIs on several steps in the life cycle, including virus entry, reverse transcription, and posttranscription events.…”
Section: Research Advancesmentioning
confidence: 99%